With the greatest care, stromal interaction molecule (STIM) proteins verify what skeletal muscle is doing - Cho, Chung-Hyun; Lee, Keon Jin; Lee, Eun Hui (BMB reports, 2018)
Skeletal muscle contracts or relaxes to maintain the body position and locomotion. For the contraction and relaxation of skeletal muscle, Ca2＋ in the cytosol of skeletal muscle fibers acts as a switch to turn on and off a series of contractile proteins. The cytosolic Ca2＋ level in skeletal muscle fibers is governed mainly by movements of Ca2＋ between the cytosol and the sarcoplasmic reticulum (SR). Store-operated Ca2＋ entry (SOCE), a Ca2＋ entryway from the extracellular space to the cytosol, has gained a significant amount of attention from muscle physiologists. Orai1 and stromal interaction molecule 1 (STIM1) are the main protein identities of SOCE. This mini-review focuses on the roles of STIM proteins and SOCE in the physiological and pathophysiological functions of skeletal muscle and in their correlations with recently identified proteins, as well as historical proteins that are known to mediate skeletal muscle function. [BMB Reports 2018; 51(8): 378-387].